Choosing Here and Now versus There and Later: The Moderating Role of Psychological Distance on Assortment Size Preferences - Goodman, Joseph K.; Malkoc, Selin A. (Journal of Consumer Research, 2012)
Abstract Consumers prefer larger assortments, despite the negative consequences associated with choosing from these sets. This article examines the role of psychological distance (temporal and geographical) in consumers’ assortment size decisions and rectifies contradicting hypotheses produced by construal level theory. Six studies demonstrate that while consumers prefer larger assortments when the choice takes place in the here and now, they are more likely to prefer small assortments when choices pertain to distant locations and times. This decrease in preference for large assortments is due to psychological distance increasing the similarity of the options in a category, making them appear more substitutable. This effect of psychological distance reverses when consumers consider desirability/feasibility trade-off information inherent in the assortment size decision. These findings point to important outcomes of psychological distance, resolving opposing predictions of construal level theory, and identify boundary conditions for the well-established notion that consumers are attracted to large assortments.